PCOS: A General View and Homoeopathy (Advancements in Homeopathic Research, 2025)
Polycystic ovarian syndrome is a complex  endocrinopathy affecting reproductive age,  causing obesity, menstrual irregularities, and  hyperandrogenism. It is primarily caused by chronic  persistent anovulation, which can result from various  endocrinopathies. Homoeopathy offers an effective  alternative for managing PCOS, with individualized  remedies showing efficacy in this condition. This  article will help the homoeopathic professionals to  understand PCOS better from various aspects and  select homeopathic remedies for the same.
Keywords: Homoeopathy; Medicines for Polycystic Ovarian Syndrome; Polycystic Ovarian Syndrome